Morphogenesis of Epididymis in Gaddi Sheep Foetii - Shukla, Parul (Indian Journal of Veterinary Anatomy, 2019)
The morphogenesis of epididymis was studied in sixty eight Gaddi sheep foetii ranging from 36th day to  140th day of gestation. The age of the foetii was calculated in days according to the formula: Y = 2.74 X+30.15 after measuring their crown rump length. The foetii were then divided into 4 stages i.e. stage I (31-60 days), stage II (61-90 days), stage III (91-120 days) and stage IV (121 days - till term). The formation of the tunica albuginea was observed on 65th day of gestation and its differentiation into tunica fibrosa and tunica vasculosa was evident on 70th day of gestation. The tubular and luminal diameter of epididymis increased significantly from stage II to III and thereafter decreased at stage IV of gestation. The lining epithelium of epididymal tubules was tall cuboidal type and the height of the epithelium increased with the progression of gestation. Abundant reticular and collagen fibers were seen in the capsule in stage IV of gestation. The intertubular stroma comprised of mesenchymal cells with undifferentiating smooth muscle cells, fibroblasts, blood vessels, collagen fibers and reticular fibers.